Comprehensive database of land subsidence in 143 major coastal cities around the world: overview of issues, causes, and future challenges - Laura Pedretti; Alessia Giarola; Mandy Korff; John Lambert; Claudia Meisina (Frontiers in Earth Science, 2024)
Subsidence refers to the gradual lowering or sudden sinking of the ground surface and is known to impact human lives in terms of damages to the infrastructures, utility lines, and buildings as well as changes in the surficial drainage systems and groundwater conditions. The impacts of land subsidence will be greater in the future, considering the sea level rise, population growth, intensification of coastal erosion and extreme events, as well as increase in flood risk or freshwater salinization, mostly in coastal cities. The main aim of this work is to provide an open-source, peer-reviewed, and comprehensive database identifying the main and secondary causes of land subsidence in 143 coastal cities. We highlight the potential impacts of subsidence that are still unknown in some at-risk cities and non-existence of mitigation measures. The database additionally shows that mitigation measures, specifically those addressing subsidence due to groundwater extraction, have proven successful in the past. The proposed database aims to increase the knowledge on the subsidence phenomenon and also global awareness of land subsidence issues among researchers, the scientific community, stakeholders, and policymakers in terms of urban planning and development.